The Effectiveness Of Virtual Reality Distraction On Reducing Pain Levels And Fear In Children During Injection Procedures At Rsij Cempaka Putih - Callista Afzena (International Journal of Health Engineering and Technology, 2026)
Injection procedures are a primary source of pain and fear in children that can lead to psychological trauma and hinder compliance with future medical care. This study aimed to evaluate the effectiveness of virtual reality distraction techniques in reducing pain and fear levels in children during injection procedures at Jakarta Islamic Hospital Cempaka Putih. The study employed a quasi-experimental design with a one group pretest-posttest approach involving 36 child respondents aged 3-12 years undergoing repeated injection procedures. Pain measurement used the Wong-Baker FACES Pain Rating Scale and fear used the Children's Fear Scale, with data analysis using the Wilcoxon Signed Rank Test. Results showed significant reductions in pain and fear levels after virtual reality intervention, with significance values of 0.000 for all variables. Children's assessment showed no pain increased from 16.7% to 52.8%, while no fear increased from 2.8% to 72.2%. Researcher assessments also showed consistent reduction patterns. This study concludes that virtual reality is effective as a non-pharmacological intervention to reduce pain and fear in children during injection procedures, thus can be integrated into pediatric pain management protocols in healthcare facilities.